The internationally present perpetual policy themes inhibiting development of the nurse practitioner role in the primary care context: An Australian–USA comparison. Issue 3 (June 2017) - Cashin, Andrew; Theophilos, Theane; Green, Roger
Summary: This paper plots international evidence of nurse practitioner efficacy, cost and quality against identification and discussion of barriers of nurse practitioner practice reported in the Australian and United States of America primary care contexts. It is identified that the evidence for the full utilisation of nurse practitioners as an integrated part of health service management internationally is strong, yet significant barriers remain to this happening in both countries. The barriers discussed remain consistent across time despite the evidence that has emerged. This phenomenon of consistent barriers, despite evidence of nurse practitioner efficacy, reasonable cost, and high quality is discussed as a clear example of where evidence alone is not enough to change policy.